Canine osteomyelitis caused by Leishmania sp - Infiesta Zulim, Rosalia Marina [UNESP] (2011)
Leishmaniasis is a disease emerging or re-emerging worldwide distribution (Sousa, 2008), a major impact on public health. The canine visceral leishmaniasis is an infectious parasitic zoonosis of worldwide distribution (Troncarelli, 2009), caused by a flagellate protozoan called Leishmania chagasi (Costard, 2009). Osteomyelitis can develop when the parasite reaches the bone tissue of the host via blood or continuity of adjacent soft tissue infection (Baltenperger, 2004). The histopathology of the lesions has 100% specificity when viewing the amastigote form of the parasite (Feitosa et al., 2000). A dog breed poodle, female, five years, with chronic lameness four months ago was attended by a veterinary, proceeded to the general clinical examination, radiographic evaluation of the hindquarters and the laboratory tests of enzyme immunoassay (ELISA) and indirect immunofluorescence (RIFI) for Leishmania sp. On examination, besides the enlargement of lymph nodes, the animal showed pain on flexion and extension of hind limbs. In radiographic lytic bone lesions were observed in bilateral ischial board and greater trochanter of the femur, suggestive of osteomyelitis. In specific laboratory tests for diagnosis of leishmaniasis ELISA reagent and RIFI reagent 1:40. As recommended by the Ministry of Health, the animal was euthanized. No macroscopic findings were reported during the necropsy, usually associated with leishmaniasis. The ischium bone fragments were sent for histopathological examination. There was intense proliferation of mononuclear inflammatory cells, mainly macrophages and lymphocytes. Amastigotes of Leishmania sp, were identified in the cytoplasm of some macrophages and bone tissue. In endemic areas for canine leishmaniasis, dogs with a history of intermittent lameness, and radiographic lytic bone lesions suggestive of osteomyelitis should be directed to realization of the histopathology and serologic tests for the differential diagnosis of Leishmania sp. Even without evidence of cutaneous or visceral lesions, usually associated with this disease.